2018
DOI: 10.1016/j.energy.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Energy and exergy analyses of sewage sludge thermochemical treatment

Abstract: The aim of this research was to provide a methodology for calculating the energy and exergy balances for the thermochemical treatment of sewage sludge. The results of the balances were assessed and compared for three different scenarios (torrefaction, pyrolysis and pyrolysis combined with catalytic post-treatment of the vapors). The balances were calculated based on previously published experimental data and evaluated under different conditions. The results indicated that the endothermicity decreased with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The results of the analysis are related to the specific system for which the average values of numerical parameters describing the amount and properties of sewage sludge were taken [11], [12], [14], [21], [27], [33]. Thus, the results of the analysis present a general assessment of the modified method of sewage sludge treatment, however, these may not be the same for a system with other parameters and sewage sludge with different properties than those assumed in the analysis presented in the article.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the analysis are related to the specific system for which the average values of numerical parameters describing the amount and properties of sewage sludge were taken [11], [12], [14], [21], [27], [33]. Thus, the results of the analysis present a general assessment of the modified method of sewage sludge treatment, however, these may not be the same for a system with other parameters and sewage sludge with different properties than those assumed in the analysis presented in the article.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, pyrolysis and similar processes of combustion of sewage sludge are regarded as endothermic. Nevertheless, Atienza-Martínez et al (2018) have shown lately that the necessity of pretreatment of this substrate (dehydration) moves it more to the exothermic processes, although it is still the most cost-consuming throughout the scenario. Thus, improvement of the steps allowing water removal is crucial for the future potential of the process.…”
Section: Thermal Processesmentioning
confidence: 99%
“…Two approaches were taken for performing an energy balance, using data from the experiments made at the intermediate temperature of 500 ºC. First, an energy balance considering the products (char, AP, OP, CNSL and gases) and reactant (CNS) at the standard temperature of 25 ºC was made by subtracting the standard enthalpies of formation of each one of them, which were calculated from their HHVs and the enthalpies of the corresponding combustion products, as detailed elsewhere [41,42]. The resulting value, Q py 0 , represents the standard heat for pyrolysis, i.e., without considering the sensible and latent heat of all the obtained products.…”
Section: Energy Balance and Heat For Pyrolysismentioning
confidence: 99%